To See a Moose The History of Polish Sex Education. - Kościańska, Agnieszka (European Anthropology in Translation Ser., 2021)
Guiding the reader through the development of sex education in Poland, Agnieszka Kościańska looks at how it has changed from the 19th century to the present day. The book compares how sex was described in school textbooks, including those scrapped by the communists for fear of offending religious sentiments, and explores how the Catholic church retained its power in Poland under various regimes. The book also identifies the women and men who changed the way sex was written about in the country, and how they established the field of Polish sex education.